Labor length among overweight and obese women undergoing induction of labor - Hirshberg, Adi (J Matern Fetal Neonatal Med, 2014)
OBJECTIVE: Maternal weight is thought to impact labor. With rising rates of obesity and inductions, we sought to evaluate labor times among induced women by body mass index (BMI) category. METHODS: Retrospective cohort study of term inductions from 2005 to 2010. BMI categories were: normal weight (NW), overweight (OW), and obese (Ob) (18.5–24.9, 25–29.9, ≥30kg/m(2)). Kruskal-Wallis tests compared median latent labor (LL) length and active labor (AL) length. Chi-square determined associations. Multivariable logistic regression controlled for confounders. Analyses were stratified by parity. RESULTS: A total of 448 inductions were analyzed. For nulliparas, there was no difference in LL by BMI category (p = 0.22). However, OW nulliparas had a longer AL compared to NW and Ob nulliparas (3.2, 1.7, 2.0 h, p = 0.005). For multiparas, NW had the shortest LL (5.5 h, p = 0.025) with no difference in AL among BMI categories (p = 0.42). The overall cesarean rate was 23% with no difference by BMI category (p = 0.95). However, Ob women had a greater percentage of first stage cesareans (41%) and NW had a greater percentage of second stage cesareans (55%), p = 0.06. CONCLUSION: The association between BMI and labor length among inductions differs by phase of labor and parity. BMI also influences the stage of labor in which a cesarean occurs.